2021
DOI: 10.18203/2394-6040.ijcmph20210219
|View full text |Cite
|
Sign up to set email alerts
|

Age at menarche in urban school-going girls: association between socio-economic status, BMI and physical activity

Abstract: Background: Menarche, one of the most reliable markers of pubertal maturity, is a result of a complex interplay between genetic and environmental factors. Since accelerated pubertal development is an important determinant of prognostic disease risk, especially in developing countries, attention must be focused on this important public health aspect.  Methods: Total 200 school-going girls aged between 10-15 years studying in municipal, public-funded and private schools in Mumbai were included in the study based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Table 3 contains data related to the menstrual characteristics of the participants. The age of menarche is determined by genetics, socio-economic demography, general health, and nutritional factors (20). In this study, 27.70% and 27.02% of the study population were found to have encountered menarche at the ages of 12 and 13 respectively.…”
Section: Discussionmentioning
confidence: 61%
“…Table 3 contains data related to the menstrual characteristics of the participants. The age of menarche is determined by genetics, socio-economic demography, general health, and nutritional factors (20). In this study, 27.70% and 27.02% of the study population were found to have encountered menarche at the ages of 12 and 13 respectively.…”
Section: Discussionmentioning
confidence: 61%